2008
DOI: 10.1007/s00775-008-0402-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of structural characteristics of protein Ca2+-binding sites

Abstract: To better understand the biological significance of Ca(2+), we report a comprehensive statistical analysis of calcium-binding proteins from the Protein Data Bank to identify structural parameters associated with EF-hand and non-EF-hand Ca(2+)-binding sites. Comparatively, non-EF-hand sites utilize lower coordination numbers (6 +/- 2 vs. 7 +/- 1), fewer protein ligands (4 +/- 2 vs. 6 +/- 1), and more water ligands (2 +/- 2 vs. 1 +/- 0) than EF-hand sites. The orders of ligand preference for non-EF-hand and EF-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 69 publications
7
80
0
Order By: Relevance
“…An earlier sequence alignment of CBD molecules showed that Asp927 in s3b is replaced by Ser896 in s3 (11). However, serine is rarely found to chelate with Ca 2ϩ (33). The crystal structure of s3 revealed that Asp897 is found in place to chelate with Ca 2ϩ atoms and Ser896 is pointed away from the ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier sequence alignment of CBD molecules showed that Asp927 in s3b is replaced by Ser896 in s3 (11). However, serine is rarely found to chelate with Ca 2ϩ (33). The crystal structure of s3 revealed that Asp897 is found in place to chelate with Ca 2ϩ atoms and Ser896 is pointed away from the ions.…”
Section: Resultsmentioning
confidence: 99%
“…These values vary from the few other available protein structures with square antiprismatic bound ions (see Table S4 in the supplemental material). Square antiprismatic coordination is relatively uncommon among macromolecules (33), and few are currently found in the Protein Data Bank. Ding et al described a Zn 2ϩ -bound RNase T 1 , at 1.8-Å resolution, in which six water molecules and a sole aspartate coordinate zinc (36).…”
Section: Resultsmentioning
confidence: 99%
“…The EF-hand loop between the E and the F helices coordinates Ca 2ϩ ion, usually with coordination numbers of 7 or 8 (6,(62)(63)(64). Non-EF-hand proteins utilize fewer protein ligands for coordinating Ca 2ϩ (65). Unlike ␤␥-crystallins in which the ion is exposed to the solvent with 1-4 water molecules in direct coordination with Ca 2ϩ , the EF-hand bound Ca 2ϩ is exposed to a single water molecule (Table 2).…”
Section: ؉ -Binding Motifsmentioning
confidence: 99%
“…Kirberger et al [6] carried out a statistical analysis of calcium-binding proteins, identifying the main characteristics of the calcium binding sites, different coordination number and coordination distances.…”
Section: <Figure 3>mentioning
confidence: 99%